Study of Determinant Profiles of Cutaneous Tuberculosis in Bangladesh - Rahman, Muhammad Hasibur; Ansari, Nazma Parvin; Ahmed, Khondoker Golam Sabbir; Hadiuzzaman, Md; Nipa, Nahida Islam; Islam, Md Shahidul; Bhuyan, Mohammod Kamruj Jaman; Mumu, Sabrina Alam; Chowdhury, Ishrat Jahan (Community Based Medical Journal, 2013)
The determinant spectra coupled with laboratory parameters of cutaneous tuberculosis in patients attending the Department of Dermatology and VD of the Community Based Medical College, Mymensingh, Bangladesh were studied for a period of over four years. A total of 110 patients (males, 75 and females, 35) having ages between 1 to 60 years were detected to infected. The result evidenced that skin tuberculosis is becoming mostly a disease of young patients between the ages of 16 to 30 years (44.55 %). There was a trend of appearance of Lupus vulgaris as the most common variant (49.09%) followed by Tuberculosis verrucosa cutis (29.09%). Skin tuberculosis was found more frequently in males than females (ratio 15: 7) and all patients belonged to lower socio-economic class. In 64 cases (58.18%) BCG vaccination coverage could not yield protection against cutaneous tuberculosis. Abnormal chest x-ray reports were available in 12 patients. It is interesting to note that enlargement of hilar lymph nodes, pleural effusion, ascites and generalized lymphadenopathy were not detected. Mantoux test revealed positive reactors in 100 patients (90.90%). Raised ESR (>20) was found in all patients. The validity of histopathology associated with FNAC was confirmed in 95 cases of patients (86.36%). There was evidence of Scrofuloderma in 20 patients and ICT indicated 74 positive cases. Bacteriological examination generated negative results in all cases. The response to antitubercular therapy was excellent except in 3 cases which required further monitoring of using additional drug and took much more time. The coexistence of pulmonary tuberculosis was determined in 2 patients. DOI: http://dx.doi.org/10.3329/cbmj.v1i1.13817 Community Based Medical Journal Vol.1(1) 2012 3-7